IMPLEMENTASI PAKEM PADA PELAJARAN BAHASA ARAB DI SEKOLAH DASAR ISLAM TERPADU AL-FURQON PALEMBANG - Andriyanto Andriyanto (Conciencia, 2016)
The implementation of PAKEM in Arabic lesson in integrated Islam primary school Al-Furqan of Palembang implemented in the indicator. This could be seen from the implementation of indicators on active learning, creative, effective and fun in learning Arabic language. Implication of PAKEM on Arabic lesson in integrated Islam primary school Al-Furqan of Palembang, even in the facility, learning tool, learning infrastructure, learning resources, instructional media, environmental regulation, the classroom setting, activities and the learning environment had created a fun learning atmosphere. In PAKEM, having advantages and disadvantages in Arabic language learning in integrated Islam primary school Al-Furqan of Palembang. It was seen from the advantages that it could give a freedom in learning, and made the classroom atmosphere which was dynamic and alive. Where each teacher and student were equally active. While the weakness of PAKEM was the teachers had not been able to always be active and teachers also had not been able to condition the class as well. And teachers did not understand the character of the students.